ASSESSMENT OF PHYSICO-CHEMICAL PARAMETERS OF RIVER FETE, BENUE STATE, NIGERIA - IBER, B.T; OJUTIKU, R.O (Nigerian Journal of Fisheries, 2017)
The physico-chemical properties of River Fete, Benue State, Nigeria were investigated from January to December, 2016 to determine its water quality. Water samples were collected from five sites chosen to reflect human impacts, lentic and lotic characteristics of the river ecosystem for the analysis of the parameters. Temperature, pH, conductivity and total dissolved solids were measured in situ using Hanna PH/EC/TDS tester and mercury-in-glass thermometer while Transparency was measured using secchi disc. The chemical factors were analyzed according to the standard procedure for examination of water and waste water. Two- way ANOVA at p<0.05 were used to analyze the result using GLM procedures of the statistical analysis system (SAS). The result showed water temperature ranging from 26.12oC to 27.23 oC, total hardness (156.41mg/L to 224.52mg/L). The mean values of; pH ranged from 6.62 to 7.46, dissolved oxygen 5.11mg/L to 6.96mg/L, biological oxygen demand 1.81mg/L to 2.28mg/L, Chloride 116.84mg/L to 253mg/L, the nutrients levels ranged from 0.97-1.89 mg/L for nitrate, 1.94-4.95) mg/L for phosphate and (17. 32-28.50) mg/L for sulphate. Significant variations were observed in the parameters by season and stations with nutrients being highly abundant in wet season. It can be concluded that the water is suitable for fish culture.